2018
DOI: 10.18632/oncotarget.25608
|View full text |Cite
|
Sign up to set email alerts
|

Osteolytic cancer cells induce vascular/axon guidance processes in the bone/bone marrow stroma

Abstract: Prostate and breast cancers frequently metastasize to bone. The physiological bone homeostasis is perturbed once cancer cells proliferate at the bone metastatic site. Tumors are complex structures consisting of cancer cells and numerous stroma cells.In this study, we show that osteolytic cancer cells (PC-3 and MDA-MB231) induce transcriptome changes in the bone/bone marrow microenvironment (stroma). This stroma transcriptome differs from the previously reported stroma transcriptome of osteoinductive cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The BZW2 gene affects osteosarcoma in human cell lines by accelerating bone tumor growth (Cheng et al, 2017). The EFNA5 gene was highly expressed in osteolytic human prostate or breast cancer cells that were inoculated into the bone marrow cavity of the tibial bones of immunocompromised mice (Hensel et al, 2018). Overexpression of USP45 inhibits osteogenesis or formation of new bone in human patients with glucocorticoid-induced osteonecrosis of the femoral head (Kuang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The BZW2 gene affects osteosarcoma in human cell lines by accelerating bone tumor growth (Cheng et al, 2017). The EFNA5 gene was highly expressed in osteolytic human prostate or breast cancer cells that were inoculated into the bone marrow cavity of the tibial bones of immunocompromised mice (Hensel et al, 2018). Overexpression of USP45 inhibits osteogenesis or formation of new bone in human patients with glucocorticoid-induced osteonecrosis of the femoral head (Kuang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the stromal signature of osteolytic PCa metastasis (PC-3 cell xenografts) is uniquely enriched in genes involved in vascular/axon guidance [169]. Distinct vessel morphology and the presence of vascular smooth muscle cells and mesenchymal stem cells expressing bone osteolytic factors indicate the requirement for a different metastatic niche compared to the osteoblastic stroma signature [169]. However, even in this context CAFs may play a relevant role, since intracardial inoculation of osteolytic PC-3 cells secreting IL-1β induces FSP-1 expression, a typical CAF marker, in mouse bone stromal cells [53].…”
Section: Role Of Cafs In Pca Bone Metastasismentioning
confidence: 99%
“…Among these genes, ASPN and POSTN expression has been observed also in CAFs from human bone metastatic and primary PCa ( Figure 3 B), highlighting the translational and prognostic value of these genes [ 44 ]. In contrast, the stromal signature of osteolytic PCa metastasis (PC-3 cell xenografts) is uniquely enriched in genes involved in vascular/axon guidance [ 169 ]. Distinct vessel morphology and the presence of vascular smooth muscle cells and mesenchymal stem cells expressing bone osteolytic factors indicate the requirement for a different metastatic niche compared to the osteoblastic stroma signature [ 169 ].…”
Section: Stroma In Pca Bone Metastasismentioning
confidence: 99%
“…Studies have shown that cancer cell growth competes for the hematopoietic niche in the bone marrow with the normal residing stem cells [ 3 ], and depending on the cancer cell phenotype, this may lead to either osteoblastic or osteolytic lesions. The stroma signature of osteolytic PCa cells (PC-3) xenografted intraosseously in immunocompromised mice induce a vascular/axon guidance signature [ 4 ]. The stroma signature of osteoblastic lesions from human VCap and C4-2B PCa cell lines indicated an enrichment of the hematopoietic and prostate epithelial stem cell niche.…”
Section: Introductionmentioning
confidence: 99%